Local bond stress-slip relationships between glue laminated timber and epoxy bonded-in GFRP rod. (10th May 2018) - Ling, Zhibin; Yang, Huifeng; Liu, Weiqing; Zhu, Shijun; Chen, Xin
Highlights: Pull-pull tests were conducted to investigate the bond behaviour between glulam and GFRP rod. The specimens with glued-in GFRP rod generally showed brittle failure mode. The local bond stress-slip relationships at different locations differ from each other. The local bond-slip stiffness distributed non-uniformly along the bonded length. Abstract: This paper presents an experimental campaign conducted on the glue laminated timber (glulam) joints with epoxy bonded-in GFRP rod aiming to investigate the bond-slip mechanism between glulam and GFRP rod. The tests were conducted in pull-pull configuration. To measure the axial strains of GFRP rods during testing, strain gauges were internally installed in the GFRP rods in advance of bonding. The test results were summarized and discussed in terms of typical failure modes, load-slip behavior, distributions of GFRP rod strain, bond stress and relative slip. The local bond stress-slip relationships at different locations along the bonded length were obtained based on the obtained bond stress and relative slip distributions. It was founded that the local bond stress-slip relationships at different locations differ from each other. The local bond stress-slip curves near the loaded end are generally stiffer than those close to the anchorage end, which indicates that it might not be reasonable to do finite element modelling using an unified bond-slip law. The local bond-slip stiffness distributed nonuniformly along the bonded length confirming the differences among the local bond-slip relationships at different locations again. Finally, the analytical models were used to predict the bond-slip behaviour of the specimens. The results showed that the analytical models can predict the bond-slip behaviour between the glulam and the GFRP rod effectively. This study expanded the data base of the timber joints with glued-in rod and provided some references for the structural analysis and design of the glued-in FRP timber joints.